Sardinian deer increase feeding diversity within sheltering vegetation in a fragmented Mediterranean landscape - Sabine Aboling; Fahad Ahmed; Gunnar Kreisel; Josef Kamphues; Maria Grazia Cappai (Scientific Reports)
Abstract This study was carried out to investigate the feeding behavior of Sardinian deer roaming within a site of community interest (SCI, ITB042250), on Sardinian Island (39° 51’ N 8° 45’ E). Crop fields bordering the natural environment (wood forest and Mediterranean macchia, where the reserve of Sardinian deer partly overlaps) were monitored and turned into a living lab. The interest on wildlife-related crop damage poses a significant economic challenge, while anthropogenic pressures, such as urbanization and agricultural practices, increasingly impact wildlife by limiting habitat, feeding source diversity and access, and space distribution. In view of this, dietary habits of a group of 25 Sardinian deer (Cervus elaphus corsicanus Erxleben, 1777) were studied over an area of 45 hectares, in spring and autumn over two consecutive years. Within six representative sites (habitats) of investigation (SOI = 3 ha), two transects of 20 × 10 m per SOI, amounting to 240 m², served as parts of these sites, respectively, and were analyzed as to floristic composition and dominating plants. The number of freshly browsed/grazed plants by missing shoots was counted and assumed as signs of foraging activity of the Sardinian deer. The evenness of the dietary preference per habitat was calculated with the number of missing shoots and the number of plant species selected. The Mediterranean macchia accounted for the highest species (n = 76); crop field the fewest species (n = 19). Plants showing foraging signs by Sardinian deer ranged between n. 5 out of 46 species (10.9%) in the fallow and n. 6 out of 19 species (31.6%) in the crop field. Complementary feeding based on the availability of floristic diversity revealed to align to the typical foraging behavior of intermediate feeder in all SOIs: the higher the species, the higher the number of foraged species (ρ = 0.86). Sardinian deer foraged on n. 35 out of 129 plant species present (27.1%) within the whole transect area. Data highlight two feeding behavior: 1)high evenness-feeding (less foraging on high number of plant species, respectively: fallow, crop field, macchia border); 2) low evenness-feeding (large foraging on few species, Avena or Cytisus: field, bordering both macchia and fallow, macchia).The Sardinian deer fed on every SOI, with highest consumption in the macchia and least in oat open field. The feeding behavior of Sardinian deer confirms the ability to adapt to the varying vegetation in each habitat, respectively, by seeking energy and nutrients on the one hand and shelter on the other, by limiting the preference for crop field center.